2007
DOI: 10.1016/j.bbamcr.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAP-Kinases pathway regulation, function and role in human diseases

Abstract: Mammalian p38 mitogen-activated protein kinases (MAPKs) are activated by a wide range of cellular stresses as well as in response to inflammatory cytokines. There are four members of the p38MAPK family (p38alpha, p38beta, p38gamma and p38delta) which are about 60% identical in their amino acid sequence but differ in their expression patterns, substrate specificities and sensitivities to chemical inhibitors such as SB203580. A large body of evidences indicates that p38MAPK activity is critical for normal immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
1,096
0
16

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,198 publications
(1,133 citation statements)
references
References 238 publications
21
1,096
0
16
Order By: Relevance
“…Thus, MAPK pathway deregulation may be implicated early in breast cancer development, and may differentiate PM from HN epithelium. The MAPK functions in cell cycle and transcriptional regulation and in the immune response may thus inhibit tumourigenesis (Bradham and McClay, 2006;Cuenda and Rousseau, 2007), Therefore, it is not surprising to see a higher expression of genes in this pathway in NlEpi from women without breast cancer (RM and perhaps PM samples). Alternatively, a FOS JUN BAG5 PTG2 CD93 CLU IER3 AHNAK BAG5 FOS FRZB IER3 IF16 IL6 JUN KLF4 ZFP36 YVVHAZ TXNIP TNC SPRY1 SNF1LK SEMA5A PTGS2 PRDX2 NR4A2 NR4A1 MCL1 MARCKS MAFF FRZB IER3 IFI6 IL6 JUN KLF4 MAFF MCL1 NR4A1 NR4A2 NR4A3 ZFP36 YWHAZ YWHAZ SAV1 PRDX2 NR4A1 MCL1 IL6 IFI6 TXNIP TRO TNC SPRY1 SNF1LK SEMA5A PTP4A1 PTGS2 PRDX2 AHNAK ABLIM1 BAG5 BST2 BTG2 CLU EGR1 ETS2 FHL1 FOS FOSB Figure 4 Gene list analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MAPK pathway deregulation may be implicated early in breast cancer development, and may differentiate PM from HN epithelium. The MAPK functions in cell cycle and transcriptional regulation and in the immune response may thus inhibit tumourigenesis (Bradham and McClay, 2006;Cuenda and Rousseau, 2007), Therefore, it is not surprising to see a higher expression of genes in this pathway in NlEpi from women without breast cancer (RM and perhaps PM samples). Alternatively, a FOS JUN BAG5 PTG2 CD93 CLU IER3 AHNAK BAG5 FOS FRZB IER3 IF16 IL6 JUN KLF4 ZFP36 YVVHAZ TXNIP TNC SPRY1 SNF1LK SEMA5A PTGS2 PRDX2 NR4A2 NR4A1 MCL1 MARCKS MAFF FRZB IER3 IFI6 IL6 JUN KLF4 MAFF MCL1 NR4A1 NR4A2 NR4A3 ZFP36 YWHAZ YWHAZ SAV1 PRDX2 NR4A1 MCL1 IL6 IFI6 TXNIP TRO TNC SPRY1 SNF1LK SEMA5A PTP4A1 PTGS2 PRDX2 AHNAK ABLIM1 BAG5 BST2 BTG2 CLU EGR1 ETS2 FHL1 FOS FOSB Figure 4 Gene list analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian p38 mitogen-activated protein kinases (MAPKs) are activated by a wide range of cellular stresses, both acute and chronic (Cuenda and Rousseau 2007;Johnson and Lapadat 2002). As p38MAPK activity is critical for normal immune and inflammatory responses, different components of this pathway have become potential targets for the treatment of autoimmune and inflammatory diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, a recent study showed the role of p38 MAPK as a tumor suppressor. 29 This involves promoting cell growth arrest and inducing cell apoptosis. 30 Bortezomib-mediated induction of apoptosis in leukemia cells has been linked to JNK and p38MAPK activation.…”
Section: Discussionmentioning
confidence: 99%